Observations of biennial reproduction in Caribbean reef sharks ‘Carcharhinus perezi’ - Campbell, Beckah A.; Shipley, Oliver N.; Jones, Taeler R.; Gallagher, Austin J.; Sulikowski, James A. (Frontiers in Marine Science, 2024)
Effective management and conservation of threatened species biodiversity requires knowledge of reproductive biology, such as cyclicity, mode, and age at maturity. We combined reproductive endocrinology and in-situ ultrasonography to examine reproductive characteristics of female Caribbean reef sharks Carcharhinus perezi, a widely distributed, threatened marine predator which remains largely understudied throughout its range. Unique to this study was the opportunity to conduct longitudinal assessments of two individuals, recaptured across multiple seasons during sampling in The Bahamas. Within-individual, paired hormone analyses and insitu ultrasounds of female sharks that were confirmed as either pregnant, non-pregnant, or reproductively active, suggest a biennial reproductive cycle for Carcharhinus perezi. This unique opportunity to assess the reproductive biology of the same individuals over time underscore the importance of repeated sampling for elucidating population reproductive cyclicity of highly mobile sharks in the wild. 1 Introduction Elasmobranch fishes exhibit conservative life-history traits including slow growth, late maturity, and low reproductive output, rendering them highly vulnerable to overfishing (Stevens et al., 2000). As a result, approximately one-third of all living elasmobranch species are listed as "Vulnerable" to "Critically Endangered" and 14% considered as "Data Deficient" by the International Union for the Conservation of Nature (IUCN) 2022 Red List (IUCN, 2022). Understanding components of a species' reproductive biology (i.e., age-at-maturity, gestation period, reproductive mode, reproductive cyclicity) and life-history strategies related to reproduction are essential for effective management of wild populations (Natanson et al., 2019).